Wacana Persuasi Dalam Sms Penawaran Pada Provider Telekomunikasi Dan Relevansinya Terhadap Pengembangan Bahan Ajar Bahasa Indonesia Siswa Smp - Imami, Yunita Putri, Dra. Atiqa Sabardila, M, Hum (2017)
The aim of this research is to analyze: (1) describing language's characteristic used in the persuasive discourse in Short Message offering on telecommunication's provider, (2) identifying the message contents containing in the persuasive discourse in Short Message Service offering on telecommunication's provider, and (3) explaining the relevance in the persuasive discourse in Short Message offering on telecommunication's provider as teaching material development Indonesian language junior high school students. This study is a qualitative research. The source of data in this study is written language taken form electronic media, that is Short Message offering. The techniques used to collect the data are documentation, scrutinize, and taking note. The techniques of data analysis used are aggregated elements of determinants padan techniques, extension techniques on the method agih, and sign reading techniques. There are three findings of this study. (1) The language's characteristic used in the persuasive discourse in Short Message offering is the usage of foreign and local language, the usage of abbreviation, and the usage of affixed words, (2) the contens of the message contained in the persuasive discourse are confirmation, command, suggestion, and persuation, and (3) the relevance of persuasive discourse in the Short Message offering towards Indonesian language teaching material development of eighth grade.